2014
DOI: 10.1517/14740338.2014.914170
|View full text |Cite
|
Sign up to set email alerts
|

Ginger for prevention of antiretroviral-induced nausea and vomiting: a randomized clinical trial

Abstract: Ginger was effective in ameliorating of antiretroviral-induced N/V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…[39] Nutraceutical properties of ginger are important to food processing and the pharmaceutical industries. According to the previous studies, [3,40,41] the clinical dosage of ginger was at 0.5-6 g per 70 kg per day (7.14-85.71 mg kg −1 ), therefore, the dosage of 6-Gin was converted at 0.1535-1.843 mg kg −1 . [42] The human equivalent dose of 6-Gin given to the mice (10 and 20 mg kg −1 ) in this study was 0.677-1.354 mg kg −1 based on the formula by Reagan-Shaw et al [43] Therefore, the concentration used in this study was relevant from a nutritional point of view.…”
Section: Discussionmentioning
confidence: 99%
“…[39] Nutraceutical properties of ginger are important to food processing and the pharmaceutical industries. According to the previous studies, [3,40,41] the clinical dosage of ginger was at 0.5-6 g per 70 kg per day (7.14-85.71 mg kg −1 ), therefore, the dosage of 6-Gin was converted at 0.1535-1.843 mg kg −1 . [42] The human equivalent dose of 6-Gin given to the mice (10 and 20 mg kg −1 ) in this study was 0.677-1.354 mg kg −1 based on the formula by Reagan-Shaw et al [43] Therefore, the concentration used in this study was relevant from a nutritional point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Still, ginger may have a beneficial effect in gynecological patients, according to the results from Apariman et al, Chaiyakunapruk et al, Phillips et al, and Bone et al [58][59][60][61]. Finally, in the study by Dabaghzadeh et al, the researchers primally examined the effect of ginger and demonstrated its benefit on the prevention of nausea and vomiting induced by an antiretroviral regimen (p = 0.001) [62]. Efficacy on motion sickness and vertigo was also examined in several studies, with results indicating different aspects between the studies.…”
Section: Yesmentioning
confidence: 99%
“…Evidence to support efficacy of ginger in prevention and treatment of chemotherapy‐induced nausea and vomiting is lacking. However, ginger showed promising effect on preventing postoperative nausea and vomiting at least as add‐on therapy (Dabaghzadeh et al ., , ). Efficacy of ginger for prevention of antiretroviral‐induced nausea and vomiting has been recently evaluated, and the results are promising (Dabaghzadeh et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory effects of gingerol on some receptors at peripheral and central levels have been suggested as probable mechanisms (Langner et al ., ; Pertz et al ., ; Qian et al ., and Qian et al ., ). Effects of ginger as a partially safe herbal product with minimal clinically significant drug interactions in prevention of postoperative, chemotherapy, and antiretroviral‐induced nausea and vomiting have been evaluated (Mahesh et al ., ; de Pradier, and Dabaghzadeh et al ., , ).…”
Section: Introductionmentioning
confidence: 99%